Forming-free, bipolar resistivity switching characteristics of fully transparent resistive random access memory with IZO/α-IGZO/ITO structure - Lo, Chun-Chieh; Hsieh, Tsung-Eong (Journal of physics. D, Applied physics, 2016)
Fully transparent resistive random access memory (TRRAM) containing amorphous indium gallium zinc oxide as the resistance switching (RS) layer and transparent conducting oxides (indium zinc oxide and indium tin oxide) as the electrodes was prepared. Optical measurement indicated the transmittance of device exceeds 80% in visible-light wavelength range. TRRAM samples exhibited the forming-free feature and the best electrical performance (VSET  =  0.61 V; VRESET  =  −0.76 V; RHRS/RLRS (i.e. the R-ratio)  >103) was observed in the device subject to a post-annealing at 300 °C for 1 hr in atmospheric ambient. Such a sample also exhibited satisfactory endurance and retention properties at 85 °C as revealed by the reliability tests. Electrical measurement performed in vacuum ambient indicated that the RS mechanism correlates with the charge trapping/de-trapping process associated with oxygen defects in the RS layer.